2008
DOI: 10.1063/1.2834370
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermal conductivity by aggregation in heat transfer nanofluids containing metal oxide nanoparticles and carbon nanotubes

Abstract: An approximately 10% increase in the thermal conductivity (TC) of heat transfer nanofluids containing metal oxide nanoparticles and carbon nanotubes has been determined with very low percentage loading (around 0.02wt%) of these two nanomaterials. These fluids are very stable and the viscosity remains approximately the same as water. A possible explanation for these interesting results is the aggregation of metal oxide particles on the surface of nanotubes by electrostatic attraction and form the aggregation ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(43 citation statements)
references
References 14 publications
1
39
0
Order By: Relevance
“…They observed greater thermal conductivity enhancement when the magnetic field was applied, which suggests that the nanotubes aligned to form conductive paths within the fluid. Hong et al 58 and Wensel et al 59 observed similar behavior in dilute nanofluids containing both iron oxide and SWCNTs. However, the thermal conductivity decreased after some time in the magnetic field due to agglomeration and settling of particles.…”
Section: Effect Of Particle Arrangement In Suspensionsupporting
confidence: 51%
“…They observed greater thermal conductivity enhancement when the magnetic field was applied, which suggests that the nanotubes aligned to form conductive paths within the fluid. Hong et al 58 and Wensel et al 59 observed similar behavior in dilute nanofluids containing both iron oxide and SWCNTs. However, the thermal conductivity decreased after some time in the magnetic field due to agglomeration and settling of particles.…”
Section: Effect Of Particle Arrangement In Suspensionsupporting
confidence: 51%
“…When analyzing X-ray scattering, particles in the liquid are complicated by the interference among X-rays that are elastically scattered from individual particles. Wensel et al [116] evaluated the stability of nanofluids by visually inspecting the dispersion stability of nanofluids with nanotubes and metal oxide particles. Chiesa and Simonsen [117] utilized TEM (transmission electron microscopy) and alumina/oil, and obtained stable nanofluids when the nanoparticles were well distributed.…”
Section: Stability Of Nanofluidsmentioning
confidence: 99%
“…A number of stabilizers have been studied to improve the solubility of CNT and other carbon allotropes in variety of solvents [29,34]. Major concerns on the use of surfactant are mostly associated to the low temperature degradation, generation of undesired foam and high surfactant/CNT loading ratio requirement which further insulate the particles [33,35,36]. These further implicate the thermal and electrical performance as well as increasing the nanofluid viscosity especially with the use of high molecular weight polymers [37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%